Intellectual dynamics of knowledge quest in the early Muslim intellectual heritage - Hashi, Abdurezak Abdulahi (2011)
Intellectual dynamics refer to the academic behaviors and manners of knowledge acquisition through which early Muslims studied the natural phenomenon, societies and religious teachings. Intellectual dynamics of the early Muslim heritage was marked by genuine spirit of scientific quest and profound enthusiasm of knowledge quest. Among noticeable intellectual dynamics of the Muslim scientific quest are, among others, genuine spirit of knowledge acquisition, academic freedom, rationalism, universality of knowledge quest, tolerance and scientific method. This paper aims to analyze such intellectual features and indicate their contemporary relevance and revival.